Penerapan Strategi Pemasaran Berkelanjutan Untuk Mencapai Keunggulan Kompetitif di Akademi Komunitas Darussalam - Muh Khotibul Umam; Muhammad Sidiq Purnomo (NAAFI: JURNAL ILMIAH MAHASISWA, 2024)
This study discusses the impact of implementing sustainable marketing strategies and utilizing digital media on the image of Darussalam Community Academy in the eyes of the community and prospective students. This study aims to analyze how the integration of sustainability values and digital media utilization affects the image of the institution as well as identify challenges in its implementation. This research uses a descriptive qualitative method with data collection techniques through in-depth interviews, observation, and documentation studies. The collected data were analyzed using thematic analysis techniques to identify patterns and meanings of the findings. The results showed that the integration of sustainability values, such as environmental awareness, social responsibility, and transparency, as well as the utilization of digital media through platforms such as social media and websites, had a positive impact on improving the image of Darussalam Community Academy. However, there are still obstacles such as limited competent human resources, lack of consistency in strategy implementation, and limited utilization of digital analytical tools. This research emphasizes the importance of management support, continuous training, and strengthening a systematic framework to ensure the effectiveness of sustainable and digital marketing strategies at Darussalam Community Academy. With improvements in these aspects, the academy is expected to increase its competitiveness and strengthen its positive image in the future.